Composition for forming ceramic electrolytes and resulting electrolytes - Patents.com

JP2024512695A5Pending Publication Date: 2025-04-02LINA ENERGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023560464
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-29
Filing Date
2022-03-25
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

Existing methods for forming ceramic electrolytes, such as β''-alumina and Nasicon, require high sintering temperatures above 1200°C, which are costly and can cause distortion or brittleness, necessitating additional processing and increased production costs.

Method used

A composition comprising sodium ion conductive ceramic particles and a low proportion of transition metal oxides, such as copper, titanium, and niobium oxides, acts as a sintering aid, reducing the sintering temperature to below 1100°C without compromising ionic conductivity.

Benefits of technology

The use of transition metal oxides as sintering aids achieves significant densification at lower temperatures, improving the ceramic's mechanical strength and reducing production costs while maintaining sodium ion conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

A composition for forming a sodium ion conductive electrolyte structure is provided, comprising particles of a sodium ion conductive ceramic in combination with particles of at least one transition metal oxide, such as copper oxide, titanium oxide, and niobium oxide or iron oxide, or precursors of these oxides, the metal oxide comprising 5% or less by weight of the particle. The sodium ion conductive ceramic may be of the type known as Nasicon, or β″-alumina. The metal oxide may comprise 2% or less by weight of the particle. The metal oxide acts as a sintering aid that allows densification to be achieved at reduced sintering temperatures without significantly adversely affecting the electrical properties of the sintered ceramic. The invention also encompasses an electrode structure produced by sintering the composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to compositions or mixtures for forming ceramic electrolytes for use in electrochemical cells, and the resulting electrolytes. [Background technology]

[0002] Several different types of electrochemical cells are known that use ceramic electrolytes. These include cells in which the electrolyte must be hot to provide sufficient conductivity; and cells in which the electrodes must be hot for the electrode components to be liquid. One such type of cell is the molten sodium metal halide rechargeable battery, e.g., the sodium / nickel chloride cell, sometimes referred to as the ZEBRA cell (see, e.g., J. L. Sudworth, “The Sodium / Nickel Chloride (ZEBRA) Battery (J. Power Sources 100 (2001) 149-163). The sodium / nickel chloride cell incorporates a liquid sodium anode separated from the cathode by a solid electrolyte that conducts sodium ions. The solid electrolyte may consist of, for example, beta alumina. The cathode contains nickel, nickel chloride and sodium tetrachloroaluminate, which is liquid during use and acts as a secondary electrolyte, allowing the transport of sodium ions from the nickel chloride to the solid electrolyte. The cathode also incorporates aluminum powder. Substitution of some of the nickel with other transition metals, such as iron, can provide additional discharge voltage levels. The cell operates at temperatures that are typically below 350 °C, but must be above the melting point of sodium tetrachloroaluminate, which is 157 °C, and the operating temperature is typically between 270 °C and 300 °C. During discharge, the usual reactions are: Cathode (positive electrode): NiCl2+2Na + +2e - →Ni+2NaCl Anode (negative electrode): Na → Na + +e - The overall result is that anhydrous nickel chloride (in the cathode) reacts with metallic sodium (in the anode) to produce sodium chloride and nickel metal; the cell voltage is 2.58 V at 300° C.

[0003] A modified type of ZEBRA cell, a molten sodium-nickel chloride rechargeable cell, is described in WO 2019 / 073260. It uses an electrolyte element comprising a perforated sheet of non-reactive metal and an impermeable layer of sodium ion conducting ceramic bonded to one side of the perforated sheet. In this electrolyte element, strength is thus provided by the metal sheet, which allows the thickness of the electrolyte to be significantly reduced compared to that required in conventional ZEBRA cells. This results in a cell or battery that can function well at significantly lower temperatures, for example below 200°C. Furthermore, the significantly thinner layer of ceramic also significantly reduces the stress induced by heating from ambient temperature, allowing the ramp-up time from ambient temperature to be only a few minutes. These are both commercially advantageous. The impermeable ceramic layer is deposited on and bonded to the perforated metal sheet, sometimes by a porous ceramic sublayer. A similar electrolyte is described in GB2019388.4=PCT / GB2021 / 053215, filed December 9, 2020. In this application, a ceramic sheet acting as an electrolyte is in contact with a perforated metal sheet over substantially its entire area to provide support for the ceramic sheet, but in this application the ceramic sheet is formed separately rather than by deposition onto the metal sheet.

[0004] A suitable ceramic for conducting sodium ions is that called Nasicon; another suitable ceramic is alumina, more specifically β''-alumina, the β'' phase of Na2O.5Al2O3. Electrolytes of this latter material are sometimes called BASE, "Beta Alumina Solid Electrolyte". Nasicon is a family of materials with the abbreviation "Na Super-Ionic Conductor" and have the formula NaMP3O 12 where M represents one or more metal ions with a wide variety of possible valences. Nasicon materials have a structure consisting of a three-dimensional framework of corner-sharing MO6 octahedra and PO4 tetrahedra, but the crystal structure is determined by the composition. One such material is Na3Zr2(SiO4)2(PO4). Formation of the electrolyte structure of β''-alumina or Nasicon requires the formation of layers of granular material and firing to form a coherent structure and achieve densification. Firing temperatures are above 1200°C for Nasicon and typically 1600°C for β''-alumina. It would be desirable to achieve sintering and densification at lower temperatures, as temperatures below 1100°C are more compatible with high temperature stainless steels and temperatures below 1200°C would reduce both capital and running costs of the furnace. Furthermore, processing at high temperatures above 1200°C can result in twisting of the ceramic layer or the substrate on which it is formed, a problem exacerbated if the furnace is operated above 1400°C. It is essential that the layer remain flat for effective performance, packing and sealing within the cell. Any such twisting can require additional processing such as grinding, cutting and polishing, increasing production costs and introducing variability due to the brittleness of the material. Importantly, firing at temperatures below 1200° C. would negate the need for any post-sintering mechanical interaction with the sodium ion conducting layer. Summary of the Invention

[0005] According to the present invention there is provided a composition for forming a sodium ion conducting electrolyte structure comprising particles of a sodium ion conducting ceramic and particles of at least one transition metal oxide, or at least one precursor for a transition metal oxide, wherein the one or more transition metal oxides constitute 5% by weight or less of the weight of the particles. Thus, the composition is a mixture of these two types of particles, namely particles of sodium ion conducting ceramic and a small proportion of particles of transition metal oxide (or precursor). The or each transition metal oxide acts as a sintering aid, thereby reducing the temperature required for densification of the sodium ion conducting ceramic particles. The transition metals may include copper, titanium and / or niobium. Other transition metals that may be used are hafnium, scandium, cobalt or vanadium. Another suitable transition metal is iron. The use of sintering aids in ceramics is well known. Typically, the addition of sintering aids lowers the sintering temperature, but has material interactions that can substantially alter the properties of the host material. The present invention provides sintering aids that significantly lower the sintering temperature of both β''-alumina and NASICON, and importantly, do not harm the sodium ion pore structure within the ceramic. Thus, they do not reduce the ionic conductivity of the densified ceramic. Furthermore, the method of addition of these sintering aids to the sodium ion conducting host has only a minor effect on the methodology used to develop thick films of the sodium conducting material. Such methods include, but are not limited to, screen printing, spraying, electrophoretic deposition, tape casting, and calendering.

[0006] Surprisingly, it has been found that the low proportions of metal oxides used in the present invention result in a significant reduction in the temperatures required for sintering and densification without significantly decreasing the ionic conductivity of the sintered material. Sometimes metal oxide particles can be produced on the surface of the sodium ion conducting ceramic by thermal decomposition of precursor salts (e.g., copper (II) nitrate as a precursor for copper oxide, or ferric nitrate as a precursor for iron oxide) to produce ultrafine intermixing of the metal oxide, which acts as a sintering aid, with the particles of the sodium ion conducting ceramic. Since the ceramic particles are in the form of a powder, this may require the addition of an aqueous or alcohol-based solution of the precursor salt to the powder. When the transition metal oxides are oxides of copper, titanium and niobium, the proportion of copper oxide may be greater than that of titanium oxide, which in turn may be greater than that of niobium oxide, for example, their ratio by mass may be 4:2:1 for the oxides CuO:TiO2:Nb2O5.

[0007] Improved densification with Nasicon is achieved when particles of one or more transition metal oxides, such as oxides of copper, titanium and niobium, or iron oxide, constitute no more than 3% by weight, preferably no more than 2% by weight, but typically greater than 0.5% by weight, and sometimes greater than 1% by weight, of the particles in the composition. For best results, the metal oxide particles should be smaller than the sodium ion conductive ceramic particles so that they fit into the voids between the sodium ion conductive ceramic particles during processing to form the electrolyte structure. The metal oxide particles can be nanoparticles with a size of less than 50 nm, for example 30 nm or 20 nm, so that they are less than one tenth the size of the ceramic particles. The ceramic particles can have a monomodal particle size distribution with a D95 of less than 2 μm, for example about 1 μm. The D50 of these particles can be less than 0.5 μm, for example about 0.40 or 0.35 μm. The metal oxide particles preferably have a median size less than one tenth the size of the sodium ion conductive ceramic particles. This ensures good packing of the ceramic particles, as the metal oxide particles are small enough to fit into the voids between the ceramic particles. In situ generation of transition metal oxides from precursors can provide the benefits of both a uniform distribution of transition metal oxide particles around every ceramic particle, and very small nano-sized particles of the oxide. For example, iron oxide particles can be made by heating ferric nitrate, and the resulting iron oxide particles can be less than 10 nm. To ensure densification, the mixture of ceramic particles and metal oxide particles, once formed into the desired shape (e.g. pellets or layers), is subjected to consolidation, e.g. by compression, and then fired. Preferably, this achieves a green density between 50% and 65% of full density, or even higher. Consolidation ensures that a high green density is achieved before firing, thus avoiding residual porosity and also the formation of cracks during sintering.

[0008] In a second aspect, the present invention provides an electrolyte structure formed by sintering the above composition to achieve densification. The present invention also provides an electrolyte structure comprising a densified sodium-ion conducting ceramic containing at least one transition metal oxide constituting 5% or less by weight of the electrolyte structure, the structure consisting of sodium-ion conducting ceramic particles and transition metal oxide particles at the interfaces between adjacent particles of the ceramic, the transition metal oxide being, for example, iron oxide or a combination such as oxides of copper, titanium and niobium. The electrolyte may be supported by or deposited on a metal sheet or foil with holes or perforations. The electrolyte may include a porous layer formed on a perforated metal sheet and an impermeable layer formed on the opposite side of the porous layer. Alternatively, there may be multiple ceramic layers with progressively lower levels of porosity covered by impermeable layers. For example, there may be three ceramic layers: a porous layer formed on a perforated metal sheet, a less porous layer formed on the outer surface of the porous layer, and an impermeable layer formed on the outer surface of the less porous layer. Different sizes of ceramic particles and different ratios of transition metal oxides may be used to obtain different porosities. The invention will now be described in further detail, by way of example only, and with reference to the accompanying drawings in which: [Brief description of the drawings]

[0009] [Figure 1] 1 shows dilatometry data for pellets of various compositions sintered to 1000° C. [Diagram 2] 1 shows dilatometry data for pellets of various compositions sintered to 1050° C. [Diagram 3] 1 shows dilatometry data for pellets of various compositions sintered to 1100° C. [Figure 4] A 10,000x magnification image of the fracture surface of a Nasicon pellet sintered to 1000°C for 1 hour with the addition of an oxide sintering aid is shown. [Diagram 5] A 10,000x magnification image of the fracture surface of a Nasicon pellet sintered to 1100°C for 1 hour with the addition of oxide sintering aids is shown. [Figure 6] Images of the fracture surfaces of Nasicon pellets sintered to 1000° C. and 1100° C. for 1 hour without the addition of oxide sintering aids are shown at 10,000 times magnification. [Figure 7] 4 shows DC conductivity measurements for Nasicon pellets of various compositions at room temperature. [Figure 8] 4 shows DC conductivity measurements for Nasicon pellets of various compositions at 250° C. [Figure 9] 13A-13C are schematic diagrams illustrating electrical impedance data for Nasicon pellets produced with and without sintering agent, the electrical impedance data being graphically presented as Nyquist plots showing the variation of imaginary impedance with real impedance. [Figure 10] 1 shows a cross-section of a Nasicon electrolyte made on FeCralloy steel using Nasicon with 2% Fe (nitrate decomposition pathway) sintering aid. EXAMPLES

[0010] Example 1 - Substratum β''-alumina based electrolyte layers were prepared by forming a slurry containing propan-2-ol and β''-alumina particles with an average diameter of 1.3 μm. The slurry was spread on a suitable substrate, dried, densified, and sintered. For experimental purposes, pellets of the same electrolyte material were made with the same composition, which was dried, formed into pellets in a die, and then compressed and sintered as the layer on the substrate. In one example, a mixture of metal oxide nanoparticles containing copper oxide (CuO), titanium dioxide (TiO2), and niobium oxide (Nb2O5) nanoparticles in a mass ratio of 4:2:1 was included in the slurry and constituted 5% of the solids by mass. In both cases sintering was carried out at 1100°C for 1 hour; this temperature is about 500°C lower than the normal sintering temperature for β''-alumina. After this sintering process, the sample containing only β''-alumina showed no signs of densification and was found to be only about 50% dense. In contrast, the sample containing both β''-alumina and the metal oxide mixture achieved about 72% densification. These densification measurements were performed on pellets since they are difficult to perform quantitatively on layers. Nevertheless, in this case the effect on the layer is clear since the ceramic powder without sintering aid remains essentially a loose powder that can be easily removed from the steel substrate, while the ceramic powder provided with sintering aid is well adhered and has strength.

[0011] Example 2 - Nasicon Layer A Nasicon-based electrolyte layer of composition Na3Zr2(SiO4)2(PO4) was prepared by forming a slurry containing propan-2-ol and particles of Nasicon. The Nasicon material was milled to give a powder with a unimodal size distribution with a d50 of less than 1 μm. In this case, the d50 was 0.36 μm, which improves packing and sintering properties. For experimental purposes, pellets of the same electrolyte material were made using the same composition in substantially the same manner, except that the composition was dried and then formed into pellets in a die, then compressed and sintered in the same manner as layers on a substrate. Sintering was evaluated using a dilatometer to measure the shrinkage of the pellets during the sintering process. In three cases, the slurry contained a mixture of metal oxide nanoparticles containing copper oxide (CuO), titanium dioxide (TiO2), and niobium oxide (Nb2O5) nanoparticles in a mass ratio of 4:2:1; in one case, the oxide mixture constituted 5% of the solids by mass, in another case, the metal oxide particles constituted 2% by mass, and in the other case, 1% by mass. In Table 1 below and in the other captions, these examples are referred to as CTN. In three further cases, iron oxide was added via a precursor decomposition route (iron nitrate 0.05M-0.5M in propan-2-ol subsequently decomposed at <300°C to form the oxide); in one case the iron oxide gave rise to a mixture that was 5% by mass of the solids, in another the iron oxide particles constituted 2% by mass, and in the other 1% by mass. In the final two cases, iron oxide was added as iron oxide nanoparticles of approximately 20 nm size; in one case the iron oxide mixture constituted 2% by mass of the solids, and in the other 1% by mass. Sintering was done by increasing the temperature to a maximum, holding it at that maximum temperature for 1 hour, and then decreasing the temperature again. This was done at maximum temperatures of 1000°C, 1050°C, or 1100°C to determine the optimum temperatures; these temperatures are about 100°C to 200°C lower than the normal sintering temperatures required for full densification of Nasicon, i.e., elimination of interconnected porosity. The densification achieved for these pellets is shown in Table 1.

[0012] Table 1 [Table 1]

[0013] Additionally, dilatometry data was obtained in each case to show how the shrinkage changes with temperature during the sintering process. Dilatometry data showing the shrinkage with temperature for these pellets is shown in Figures 1, 2, and 3 for the three highest sintering temperatures. Also included in Figures 1 and 3 are comparison graphs for the raw powder pellets, i.e., pellets made with the same Nasicon powder as above, but without any of the metal oxide sintering aids. Thus, it is not surprising that the provision of a lower proportion of the metal oxide mixture improves the densification achieved at this lower temperature; and best results are obtained with an addition of about 2 wt.%. Close examination of the derivatives of the dilatometry curves indicates that not only is the maximum rate of densification increased by the use of transition metal oxide additions, but the temperature at which this occurs is typically reduced by at least 50°C. Thus, the metal oxide particles act as sintering aids. These various results are also evident in the scanning electron microscope images in Figures 4 and 5, which show the fracture surfaces of Nasicon pellets made from compositions containing between 1% and 2% (wt) sintering aid, and in Figure 6, which shows the fracture surface of a Nasicon pellet made without the provision of sintering aid. It can be seen that in Figure 4, at 1000°C (a very low sintering temperature), there are almost no visible pores between the ceramic particles; in Figure 5, after sintering to 1100°C, there is negligible void space between the Nasicon particles. In contrast, in Figure 6, it can be seen that the material is very porous, especially for the pellets sintered at 1000°C.

[0014] The Nasicon pellets thus produced were then subjected to impedance testing at room temperature. Data was obtained at room temperature (Figure 7) and at 250°C (Figure 8) using an electrochemical impedance analyzer operating between 7 MHz and 100 Hz, which gave clear and reproducible impedance spectra. Figure 7 also shows data for the raw powder, i.e., pellets produced without the inclusion of any metal oxide sintering aid, which is labeled Raw Powder. FIG. 7 shows DC conductivity values ​​for Nasicon pellets sintered at 1000° C. and 1100° C. using a series of different sintering aids and measured at room temperature, while FIG. 8 shows DC conductivity values ​​for the same Nasicon pellets using a range of different sintering aids but measured at 250° C. Measurements of real and imaginary impedance, i.e., resistance and inductive resistance, were performed at a series of different frequencies on Nasicon pellets without sintering aid (11.68 mm diameter and 2.16 mm thickness) and Nasicon pellets made with 2% (wt) CNT sintering aid (9.39 mm diameter and 1.93 mm thickness) and the results are shown graphically as a Nyquist plot in Figure 9. The measurements shown by the filled circles are for pellets without sintering aid and the results shown by the open circles are for pellets made with sintering aid.

[0015] These measurements are consistent with literature values ​​for Nasicon, suggesting that there is no significant loss in sodium ion conductivity at 1% and 2% doping levels with metal oxide sintering aids, with only a small detrimental effect at 5%. When comparing similarly for similar densification, the overall apparent impedance would in fact appear lower due to increased densification, but the shape of the Nyquist spectrum produced (example given in Figure 9) would suggest that there was some slight increase in impedance (decrease in conductivity). Since the lower sintering temperature produces a structure with finer grains, it is expected that there may be a slight decrease in conductivity. The sintering aids fix the grain boundaries, significantly enhancing densification compared to other sintering mechanisms such as grain growth. The conductivity of the material is a combination of both bulk and grain boundary components, and therefore materials sintered at lower temperatures are expected to have a larger ratio of grain boundary resistivity to total resistivity. Thus, the decrease in conductivity is not believed to be due to the interaction of the material with the sintering aids, but rather due to having a fundamentally different microstructure. This is beneficial because the sintering aids ensure that all grains are similar (homogeneous) and small in size, which makes the ceramic significantly tougher and more durable during operation. The potential negative impact on Nasicon conductivity is likely mitigated by the fact that all sintering aids (iron, copper, titanium and niobium oxides) are viable substitutes for the Nasicon structure to form phases with sodium ion conductivity (Journal of Power Sources 273 (2015) 1056-1064).

[0016] As mentioned above, the electrolyte may comprise a layer of sodium ion conducting electrolyte supported by or bonded to a perforated metal sheet. The metal from which the perforated sheet is formed must be "inert" in the sense that it does not chemically react with the components of the cell with which it is in contact during use; it may be, for example, a metal such as nickel, or an aluminum-bearing ferritic steel (such as the type known as Fecralloy™), or a steel that forms an electrochemically conductive and adherent scale, such as a CrMn oxide scale, when heated in air. Adhesion of the ceramic to the metal may be better when using metal alloys such as Fecralloy, which form an oxide coating of alumina. The perforated sheet may be of a thickness of 1.0 mm or less, or 0.5 mm or less, for example 0.1 mm or 0.2 mm. The sheet is perforated to have a large number of through holes, the holes or pores may be of an average diameter of less than 50 μm, for example 30 μm or less, or between 50 μm and 300 μm, and may be produced, for example, by a laser drilling process or chemical etching. The through holes may have their centers spaced between 100 and 500 μm, for example 150 μm apart. The layer produced on Fecralloy steel at a firing temperature of 1050° C. for 1 hour using Nasicon with 2% iron oxide as a sintering aid produced in situ by decomposition of ferric nitrate was smooth, coherent, tightly bonded to the metal surface, and had a thickness of 1×10 -08 ~3×10 -07 It was found to be sufficiently dense to give helium permeability readings in the mbarL / s range and sufficiently leak tight for successful cell operation.

[0017] The perforated sheet may have a margin around its outer edge that is not perforated; this margin may facilitate sealing of the outer edge of the perforated plate to the adjacent components of the cell. This margin may be of a width of 15 mm or less, for example 10 mm or 5 mm or 3 mm. The electrodes may include a layer of sodium ion conducting electrolyte bonded to a perforated metal sheet with a porous ceramic layer between the metal sheet and the impermeable sodium ion conducting layer. There may be several such porous layers, for example a first porous layer on the metal surface covered by a less porous layer and finally covered by an impermeable layer. Different degrees of porosity and permeability can be achieved by using different sizes of ceramic particles and different amounts of transition metal sintering aids. The first porous layer is deposited, for example, by screen printing, the mixture of particles also including binders and flow aids; the binders and flow aids will be burned off during a binder burn-out step, typically below 300° C. at the start of the sintering process. The subsequent layer or layers may be deposited by spray coating, screen printing or electrophoretic deposition.

[0018] An example of such a layered structure is shown in FIG. 10, a scanning electron micrograph showing a cross section. The electrolyte has three layers of Nasicon. The first, most porous layer was deposited by a screen printing process, and the Nasicon particle size used in the ink had a D95 of 16.6 μm. This layer was formed in a single printing and drying process, and then fired at 1000° C. for 1 hour to give a strong but porous layer that adhered well to the substrate Fecralloy steel. A layer with an intermediate particle size of D95 of 4.7 μm was spray coated on top of this to form a structure with finer interconnected porosity. This layer contained 2% wt iron oxide added via a precursor decomposition route; it was densified under pressure and fired at 1000° C. for 1 hour to produce a strong, well-adhering, but still porous layer. Finally, this layer was spray coated with a finer particle size layer with 2% wt iron oxide addition added via the precursor decomposition route with the same specifications as used in the pellet densification study above. This layer was then fired at 1050°C for 1 hour to give a dense and permeable layer.

Claims

1. 1. A composition for forming a sodium ion conducting electrolyte structure comprising particles of Nasicon sodium ion conducting ceramic and particles of at least one transition metal oxide or at least one precursor for a transition metal oxide, wherein the one or more transition metal oxides constitute 5% by weight or less of the weight of the particles, and wherein the transition metal oxide particles comprise iron oxide, the transition metal oxide particles comprise oxides of copper, titanium and niobium, the precursor is a precursor for iron oxide, or the precursor is a precursor for oxides of copper, titanium and niobium.

2. 2. The composition of claim 1, wherein the transition metal oxide comprises oxides of copper, titanium and niobium, and the proportion of copper oxide is higher than the proportion of titanium oxide, which in turn is higher than the proportion of niobium oxide.

3. The oxide CuO:TiO 2 :Nb 2 O 5 3. The composition of claim 2, wherein the weight ratio of

4. The composition of any one of claims 1 to 3, wherein the transition metal oxide particles comprise no more than 3% by mass of particles in the composition.

5. 5. The composition of claim 4, wherein the transition metal oxide particles comprise 2% or less by weight of particles in the composition.

6. 6. The composition of claim 1, wherein the transition metal oxide particles have a smaller median size than the sodium ion conducting ceramic particles such that they fit into voids between the sodium ion conducting ceramic particles during processing to form an electrolyte structure.

7. 7. The composition of claim 1, wherein the transition metal oxide particles are nanopowder having a median size that is less than one-tenth the median size of the sodium ion conducting ceramic particles.

8. The composition according to any one of claims 1 to 6, wherein the transition metal oxide particles are produced on the surface of the sodium ion conducting ceramic particles by thermal decomposition of a precursor salt.

9. 9. An electrolyte structure formed by sintering the composition of any one of claims 1 to 8 to form a sodium ion conducting sintered ceramic.

10. 10. The electrolyte structure of claim 9, further comprising a perforated metal sheet for supporting said sintered sodium ion conducting ceramic.

11. The electrolyte structure of claim 10 including a porous layer formed on said perforated metal sheet and an impermeable layer formed on an opposite surface of said porous layer.

12. An electrolyte structure as described in claim 10, comprising at least three ceramic layers formed on the perforated metal sheet, the ceramic layers having progressively lower levels of porosity, the final layer being an impermeable layer.